Secret life of rats : rise of the rodents - Day, Trevor (Mankato, Minn. : Capstone Press, 2008)
Discusses rats' features, their behavior and lifestyle, their historical interaction with humans, and their place in modern culture.
Includes bibliographical references (p. 31) and index.
5.0
3-6
Keywords: Rats -- Juvenile literature; Rats; Rats